Model Kausal Pengaruh Fasilitas dan Konten Digital terhadap Kompetensi Teknologi Informasi Siswa dengan Mediasi Minat Belajar - Ezar Aziz; Yulianti; Wishnu Aribowo Probonegoro (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the effect of facility availability and digital content on students’ information technology competencies with learning interest as a mediating variable. A quantitative approach with a survey method was employed involving 178 students from Information Technology and Visual Communication Design programs. Data were analyzed using multiple regression, simple regression, and path analysis with SPSS 25. The results indicate that facility availability and digital content have a positive and significant effect on students’ learning interest, accounting for 68.2% of the variance. Learning interest also has a significant positive effect on students’ information technology competencies, contributing 61.5% of the variance. Furthermore, digital content shows a significant indirect effect on students’ competencies through learning interest. These findings highlight the strategic role of learning interest as a mediating variable in the causal model of digital learning and imply that improving students’ competencies requires not only adequate facilities and high-quality digital content but also instructional strategies that foster students’ learning interest.